Exchange conjunctival autograft in double pterygium - K. Sharma, Virendra; Verma, Abha; Samuel, Ena; Palod, Sapan (International Journal of Medical Research and Review, 2019)
Aims & Objectives: It is a Prospective study to determine expediency, astigmatism correction and recurrence following a modified conjunctival autograft surgical procedures in double pterygium. Material & Methods: Equal size of conjunctival grafts were taken from the opposite pterygium of the same eye and anchored with 10-0 nylon sutures. Post-operative correction of astigmatism, visual acuity and recurrence recorded in 14 eyes of 13 patients. Results: Full correction of astigmatism in 6 cases and mean 76.9% corrected in all cases, with subsequent improvement of visual acuity of one or two lines of Snellen’s chart. No recurrence recorded till 13 months. Discussion: ECA is a single time procedure, reducing hospital stay, cost and total duration of morbidity by half, with advantages of minimal tissue loss, sparing of superior conjunctiva on both nasal and temporal side and avoidance of bare sclera from the donor site of graft. Conclusion: ECA is better option in double pterygium particularly in cases of scarcity or diseased conjunctiva.